Surface roughness and mechanical properties of maxillofacial prosthetic silicone elastomers subjected to outdoor weathering in Malaysian environment - Rahman, Ahmed Mushfiqur (2019)
Silicone elastomers are widely used for fabricating maxillofacial prostheses to rehabilitate craniofacial defect. However, the average service life of a silicone elastomer can be influenced by local weather condition. In clinical practice, it is noticed that hot and humid weathers further affects the lifespan of silicone material in terms of surface degradation and tear, thereby frequent replacement of the prostheses is required. So, the aim of this study was to evaluate the surface roughness, tensile strength, and percentage elongation of different silicone elastomers subjected to outdoor weathering in the Malaysian environment. An in-vitro experimental study was performed on 120 type-II dumbbell-shaped specimens (non-weathered=15, weathered=15) made from three room temperature vulcanized (A-2000, A-2006, and A-103) and one heat temperature vulcanized (M-511) silicone (Factor II, Inc., AZ, USA) materials. For 6 months, weathered specimens were subjected to outdoor weathering in customised exposure rack, while the non-weathered specimens were kept in a dehumidifier at 25°C ± 1°C and 50 ± 5% relative humidity. Afterwards, surface roughness was measured using a profilometer (Surfcom Flex, Tokyo, Japan); tensile strength and percentage elongation was determined using Universal Testing Machine (Shimadzu, Japan). Independent t-test and one-way ANOVA was performed to compare means of the tested properties between nonweathered and weathered specimens within each silicone group, and weathered specimens among the different silicone groups respectively. After subjected to outdoor weathering at Universiti Sains Malaysia, Kelantan, Malaysia, only A-2000 silicone elastomer showed a statistically significant difference in surface roughness between non-weathered and weathered specimens (p=0.005). The silicone materials (A-2000, A-2006, and M-511) showed a statistically significant difference in tensile strength and percentage elongation values (p<0.05) after outdoor weathering compared to the non-weathered specimens. In terms of tensile strength and percentage elongation, all the elastomers were adversely affected by weathering, except for A-103 silicone which demonstrated the least changes. A-2000, A-2006, and M-511 showed higher values of mechanical properties but showed more changes after weathering. For Malaysian weather, A-103 can be suggested as a suitable silicone based on the least changes to its mechanical properties after weathering. However, the higher mechanical properties of A-2000, A-2006, and M-511 make them a viable option as well despite their significant changes after weathering. So, the clinicians need to decide whether to use A-2000, A-2006, and M-511 silicone for higher mechanical properties, or A-103 for better resistance in the Malaysian environment based on their cases.